2014
DOI: 10.1261/rna.042267.113
|View full text |Cite
|
Sign up to set email alerts
|

A single inhibitory upstream open reading frame (uORF) is sufficient to regulateCandida albicans GCN4translation in response to amino acid starvation conditions

Abstract: Candida albicans is a major fungal pathogen that responds to various environmental cues as part of its infection mechanism. We show here that the expression of C. albicans GCN4, which encodes a transcription factor that regulates morphogenetic and metabolic responses, is translationally regulated in response to amino acid starvation induced by exposure to the histidine analog 3-aminotriazole (3AT). However, in contrast to the well-known translational control mechanisms that regulate yeast GCN4 and mammalian AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Assessment of the GCN4 mRNAs in 12 fungal species revealed that uORFs range from three to six in number and are not positionally conserved (25,89). Furthermore, the mechanism of GCN4 translation control for Candida albicans is reliant upon bypass of a single inhibitory uORF whereas GCN4 in S. cerevisiae relies on a mechanism involving delayed translation reinitiation that features multiple uORFs (Fig.…”
Section: Evolutionary Conservation Of Uorf-mediated Translation Mechamentioning
confidence: 99%
“…Assessment of the GCN4 mRNAs in 12 fungal species revealed that uORFs range from three to six in number and are not positionally conserved (25,89). Furthermore, the mechanism of GCN4 translation control for Candida albicans is reliant upon bypass of a single inhibitory uORF whereas GCN4 in S. cerevisiae relies on a mechanism involving delayed translation reinitiation that features multiple uORFs (Fig.…”
Section: Evolutionary Conservation Of Uorf-mediated Translation Mechamentioning
confidence: 99%
“…The second REI-permissive uORF, uORF2 with ∼80%-90% of the uORF1 REI activity, occurs only 56-nt downstream from uORF1 and serves as a backup of uORF1 to capture all ribosomes that leaky scanned past the uORF1 AUG (Gunišová and Valášek 2014), especially during stress conditions that seem to increase the frequency of leaky scanning in general (Lee et al 2009;Raveh-Amit et al 2009;Palam et al 2011;Sundaram and Grant 2014). This ensures that the maximum capacity of this intriguing regulatory system is met.…”
Section: Introductionmentioning
confidence: 99%
“…In S. cerevisiae, cap-independent translation at IRESs in the 5′ UTR of a small subset of genes is required for invasive growth (Gilbert et al, 2007). A recent study has shown that C. albicans GCN4 is translationally regulated by a uORF (Sundaram and Grant, 2014b). The length and structure of the 5′ UTR also affect microRNA-mediated translational repression (Meijer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%